How we made professionalism relevant to twenty-first century residents. (July 2015) - Khandelwal, Aditi; Nugus, Peter; Elkoushy, Mohamed A.; Cruess, Richard L.; Cruess, Sylvia R.; Smilovitch, Mark; Andonian, Sero
Abstract The complexity of the current medical trainee work environment, including the impact of social media participation, is underappreciated. Despite rapid adoption of social media by residents and the introduction of social media guidelines targeted at medical professionals, there is a paucity of data evaluating practical methods to incorporate social media into professionalism teaching curricula. We developed a flipped classroom program, focusing on the application of professionalism principles to challenging real-life scenarios including social media-related issues. The pre-workshop evaluation showed that the participants had a good understanding of basic professionalism concepts. A post-workshop survey assessed residents' comfort level with professionalism concepts. The post-workshop survey revealed that the postgraduate trainees perceived significant improvement in their understanding of professionalism (p < 0.05). Resident responses also exposed some challenges of real-life clinical settings. There was an apparent contradiction between placing a high value on personal health and believing that physicians ought to be available to patients at any time. Participants' satisfaction with the course bodes well for continual modification of such courses. Innovative flipped classroom format in combination with simulation-based sessions allows easy incorporation of contemporary professionalism issues surrounding social media.